EFEK ANTIHIPERTENSI EKSTRAK ETANOL DAUN Eupatorium riparium Reg. PADA TIKUS SPRAGUE-DAWLEY JANTAN - , TRIS THERESIA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Eupatorium riparium Reg. plants is often used by local people as diuretics, thus it is assumed that it has diuretics effect which can decrease blood pressure. Therefore, it needs the research to investigate the antihypertensive effect of ethanol extract of E. riparium leaves in male Sprague-Dawley (SD) rats, the dose which has effect to decrease blood pressure, and to compare its effectivity to antihypertensive drug furosemide. The experiment of antihypertensive effect was done by simple random sampling design. The measurement of ratâs blood pressure was done by noninvasive method using tools CODAÂ®. Thirty male SD rats were divided randomly into six groups, each group consists of five rats. Group I is negative-control-group with Na-CMC 0,5%, Group II is hypertensive group with phenylephrine, Group III is positive-control-group with phenylephrine and furosemide, Group IV, V, and VI are groups with phenylephrine and doses of ethanol extract of E. riparium. Data based on the measurement of the blood pressure in form of AUC (Area Under Curve) has been analyzed statistically by One Way ANOVA with level of confidence 95%. The result of this experiment shows that the ethanol extract of E. riparium leaves has activity to decrease blood pressure in rats but not significantly. The dose of ethanol extract of E. riparium leaves which has the efectivity to decrease blood pressure most effectively is 100 mg/kg BW. The dose 100 and 400 mg/kg BW of ethanol extract have the effectivity which are more effective than antihypertensive drug furosemide.